2012
DOI: 10.1007/s10911-012-9243-7
|View full text |Cite
|
Sign up to set email alerts
|

A Crossroad of microRNAs and Immediate Early Genes (IEGs) Encoding Oncogenic Transcription Factors in Breast Cancer

Abstract: Signaling networks are involved in development, as well as in malignancy of the mammary gland. Distinct external stimuli activate intricate signaling cascades, which culminate in the activation of specific transcriptional programs. These signal-specific transcriptional programs are instigated by transcription factors (TFs) encoded by the immediate early genes (IEGs), and they lead to diverse cellular outcomes, including oncogenesis. Hence, regulating the expression of IEGs is of great importance, and involves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 140 publications
(159 reference statements)
0
7
0
Order By: Relevance
“…This time delay between treatment and RNA collection is likely long enough to allow transcription of immediate early genes. Immediate early gene expression has been shown to be induced within minutes following an external stimulus (35). In the MCF7 combination experiments, the majority of the genes with low p-values at time 0 in our data are known immediate early genes (35,36).…”
Section: Differential Expression Analysismentioning
confidence: 54%
“…This time delay between treatment and RNA collection is likely long enough to allow transcription of immediate early genes. Immediate early gene expression has been shown to be induced within minutes following an external stimulus (35). In the MCF7 combination experiments, the majority of the genes with low p-values at time 0 in our data are known immediate early genes (35,36).…”
Section: Differential Expression Analysismentioning
confidence: 54%
“…MiRNAs act as oncogenes or tumor suppressor when they positively or negatively regulate key genes involved in cellular processes associated to tumor genesis or progression [36]. At the same time it has been reported that several known oncogenic pathways promote carcinogenesis by a fine tuning of miRNAs expression, obtained through different mechanisms as regulation of transcription factors [37-39]. …”
Section: Discussionmentioning
confidence: 99%
“…The high concordance of replicates allowed for clear detection of differentially expressed genes (DEGs) in different conditions ( Figure S3A). To determine DEGs in MCF7, we selected a false discovery rate (FDR) cutoff at which the only DEGs at time 0 (~30 min post-treatment; see Methods) over all treatments are well-known immediate early genes (Sas-Chen, Avraham, & Yarden, 2012;Tullai et al, 2007) ; Table S1). We then used this cutoff across all time points and treatments of the fixed dose experiments.…”
Section: Time (Hours)mentioning
confidence: 99%
“…This time delay between treatment and RNA collection is likely long enough to allow transcription of immediate early genes. Immediate early gene expression has been shown to be induced within minutes following an external stimulus (Sas-Chen et al, 2012) . In the MCF7 combination experiments, the majority of the genes with low p-values at time 0+ in our data are known immediate early genes (Sas-Chen et al, 2012;Tullai et al, 2007) .…”
Section: Differential Expression Analysismentioning
confidence: 99%
See 1 more Smart Citation